Areca Nut Induces miR-23a and Inhibits Repair of DNA Double-Strand Breaks by Targeting FANCG - Tsai, Yi-Shan; Lin, Chang-Shen; Chiang, Shang-Lun; Lee, Chien-Hung; Lee, Ka-Wo; Ko, Ying-Chin (Toxicological sciences, 2011)
Previous investigations have shown that areca nut extracts (ANE) or arecoline (ARE) causes DNA damage, which in turn contributes to oral cell carcinogenesis. To understand the role of microRNA (miRNA) in ANE-associated carcinogenesis, miRNA expression profile was examined in ANE-treated normal human oral fibroblasts. Among the miRNAs changed by ANE exposure, we found that ANE-induced miR-23a overexpression was correlated with an increase of γ-H2AX, a DNA damage marker. In addition, DNA double-strand breaks (DSB) repair that was determined by an in vivo plasmid-based assay was reduced in ANE-treated or miR-23a-overexpressed cells, suggesting the role of miR-23a in DSB repair. FANCG is one of Fanconi anemia susceptibility genes that participate in DSB repair pathway to prevent chromosomal aberrations. FANCG was predicted as a candidate target of miR-23a by TargetScan algorithm. This was confirmed by ectopic overexpression or knockdown of miR-23a. The correlation between miR-23a overexpression and areca nut-chewing habit could also be found in oral cancer patients. Finally, we showed that ANE-induced/ARE-induced miRNAs were significantly associated with the functional categories of "genetic disorders" and "cancer" using network-based analyses. In conclusion, our data showed for the first time that ANE-induced miR-23a was correlated with a reduced FANCG expression and DSB repair, which might contribute to ANE-associated human malignancies.